A comparison of mode effects between face-to-face and drop-off contingent valuation surveys. Issue 3 (7th September 2015) - Ma, Hua; Liu, Hui; Gong, Yazhen; Jin, Jianjun; Mao, Xianqiang
Abstract : Purpose: – The purpose of this paper is to examine the practice potential of self-administered drop-off as a survey mode for contingent valuation (CV) studies. Design/methodology/approach: – This paper conducts an empirical comparison of mode effects of two survey methods for improved ecological services in Beijing. Data were collected from a CV survey, which has two subsamples, one using face-to-face interviews and the other employing self-administered drop-off surveys. Findings: – There is some evidence of social desirability bias in the face-to-face interviews for the participation question; however, such effects do not carry over to subjects' responses to the contribution decision. No difference is observed in sample demographics between modes. And satisficing effect is not observed in the drop-off survey in this study. Research limitations/implications: – More well-controlled mode comparisons are warranted to test the robustness of the results; and collection time effects as well as the use of drop-off surveys for environmental valuation with different levels of complexity and familiarity are worthy of further study. Practical implications: – The authors find more similarities between drop-off and face-to-face surveys than differences therefore support the practice of self-administered drop-off surveys in CVM for environmental valuation. Originality/value: – This paper adds to the limited number of well-controlled mode comparisons in the CV surveys, and contributes to a better understanding of self-administered drop-off surveys, a potential low-cost alternative to face-to-face interviews in future CV applications.